Management of Vulvovaginal Cellular Angiofibroma: A Single-Center Experience - Yuan, Zhen; Wang, Jinhui; Wang, Yongxue; Feng, Fengzhi; Pan, Lingya; Xiang, Yang; Shi, Xiaohua (Frontiers in Surgery, 2022)
Objective. The study aimed to explore the clinical characteristics, treatment, and prognosis of cellular angiofibroma in females. Methods. We performed a retrospective study in patients with vulvovaginal cellular angiofibroma treated at Peking Union Medical College Hospital between August 2012 and October 2021. Results. Eight patients were included in our study, with7 cases of vulvar tumors and 1 case of vaginal stump tumors. The median age at diagnosis was 47.5 years (range, 38-83 years). The tumors were found incidentally in two patients (2/8, 25.00%) without specific history before diagnosis surgery. Of the other six patients, the median history from onset of the mass to diagnosis was 5.5 years (range, 3-14 years). Complete excision was performed in all 8 patients. According to histopathologic examination, the median tumor size was 3.4 cm (range, 1.7-11cm). As the tumor size increased, both the operation time and postoperative length of stay increased. Gonadotrophin releasing hormone agonist was used in one case to minimize the size of the tumor, obtaining satisfactory results. Up to the last follow-up, no evidence of relapse was found to relapse in all 8 patients. Conclusions. For vulvovaginal cellular angiofibroma, the mainstay of treatment remains surgical resection without residual tumor if possible; inadvertent urinary system injury and rectum injury should be avoided to the utmost, and; enough attention should be paid to hemostasis to avoid hematoma after surgery. Before surgery, hormone receptor modulators may be considered to minimize the size of the tumor to reduce the surgery-associated risk.